Pre-hospital emergency medicine. Issue 10012 (19th December 2015) - Wilson, Mark H; Habig, Karel; Wright, Christopher; Hughes, Amy; Davies, Gareth; Imray, Chirstopher H E
Summary: Pre-hospital care is emergency medical care given to patients before arrival in hospital after activation of emergency medical services. It traditionally incorporated a breadth of care from bystander resuscitation to statutory emergency medical services treatment and transfer. New concepts of care including community paramedicine, novel roles such as emergency care practitioners, and physician delivered pre-hospital emergency medicine are re-defining the scope of pre-hospital care. For severely ill or injured patients, acting quickly in the pre-hospital period is crucial with decisions and interventions greatly affecting outcomes. The transfer of skills and procedures from hospital care to pre-hospital medicine enables early advanced care across a range of disciplines. The variety of possible pathologies, challenges of environmental factors, and hazardous situations requires management that is tailored to the patient's clinical need and setting. Pre-hospital clinicians should be generalists with a broad understanding of medical, surgical, and trauma pathologies, who will often work from locally developed standard operating procedures, but who are able to revert to core principles. Pre-hospital emergency medicine consists of not only clinical care, but also logistics, rescue competencies, and scene management skills (especially in major incidents, which have their own set of management principles). Traditionally, research into the hyper-acute phase (the first hour) of disease has been difficult, largely because physicians are rarely present and issues of consent, transport expediency, and resourcing of research. However, the pre-hospital phase is acknowledged as a crucial period, when irreversible pathology and secondary injury to neuronal and cardiac tissue can be prevented. The development of pre-hospital emergency medicine into a sub-specialty in its own right should bring focus to this period of care.